Experimental Research Dalam Metodologi Pendidikan - Rahmatullah Akbar; Weriana Weriana; Rusdy A Siroj; Muhammad Win Afgani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Research is a conscious human effort to gain new knowledge, create new knowledge, and solve or provide solutions to scientific problems. Research efforts must be carried out logically / rationally and systematically so that new information and knowledge can be obtained and useful. Experimental research is the only type of research that is more accurate/thorough compared to other studies, in determining causal relationships. This is because in experimental research the researcher can supervise (control) the independent variables both before the study and during the study. The type of research used is qualitative research, literature study. This article discusses the meaning of experimental research, the objectives of experimental research, variables in experimental research, characteristics of experimental research, various types of experimental research designs, and experimental research steps.